Redução da jornada de trabalho de assistentes sociais para 30 horas semanais: análise da experiência na Prefeitura do Município de Diadema São Paulo - Monteiro, Claudia Lima (2013)
In 2008, the professionals from the city government of Diadema, Sao Paulo, Brazil, whose occupation has complete higher education as a requirement conquered the reduction in their working hours, without wage loss, through the municipal Complementary Law 260. In turn, the federal Law 12,317, enacted on August 26, 2010, established the length of thirty working hours per week for social workers, on a national basis. The professional category s conquest established by law at the federal and municipal levels provided the choice of this dissertation s theme with consistency and relevance: the reduction in the length of working hours for social workers, which completes five years. The aim is analyzing the personal and professional repercussions of the length of thirty working hours per week from the perspective of social workers and the effects of this new professional reality. The study is based on Marxist authors and it analyzes labor as a social being s foundational category, besides transformations in the contemporary capitalist society. The methodology adopted includes literature review and documentary research on files of the respondents, the city government of Diadema, and the Union of Public Employees of Diadema. The empirical work combined the qualitative and quantitative approaches to the application of questionnaires to social workers with thirty working hours per week and semistructured interviews. The results showed that the reduction in the working hours positively reflected on the respondents personal lives and on the quality of services provided, but it didn t cause the immediate search for other employment contracts. However, the thirty working hours per week didn t result, in a significant way, in hiring of professionals and it caused intensification in the pace of work. It s essential that collective struggles are undertaken so that the implementation of working hours reduction expand the number of jobs without generating an overload for the professionals and that this achievement reaches other professional categories